Wave Energy Performance Analysis: A Comparative Study on AWS Based Wave Energy Conversion System and Well’s Turbine Based Wave Energy Conversion System - et. al., Mr.V. Loganathan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increase in installation of renewable energy power generation plants highlights the need for a research of various innovative technologies in order to achieve an improvement in current technology so that it can compete commercially. Already various renewable energies like solar energy and wind energy has reached the saturation level in terms of technological advancement. Wave energy, one of the most abundantly available energy is still in its developing stage and there is a need for incorporating novel technologies in this field. This opens the door for innovative research in this area. In this paper, two different wave energy technologies, one based on AWS (Archimedes wave swing) and the other based on Well’s turbine is compared in various aspects of performance.